Organizing on the Waterfront: The St. John's Longshoremen's Protective Union (LSPU), 1890-1914 - Chisholm, Jessie (Labour/Le Travailleur, 1990)
Abstract This article studies the initial organization and development of the St John's Longshoremen's Protective Union in the years 1890 to 1914. Undoubtedly the city's most important union the LSPU organized all waterfront workers in the city, including the numerous boys who worked on the docks, and later extended the organization to include the city's sanitation workers. Through militancy and frequent strikes the LSPU established a permanent presence in St John's. The success of the LSPU is contrasted with the experience of longshoremen in Atlantic Canadian ports to raise questions about earlier interpretations of class solidarity within merchant capital.